One man’s trash is another man’s treasure: Actor constellations to prolong the life of ‘new waste’ resources - Hansen, Andreas Kornmaaler; Laursen, Linda Nhu (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
The overconsumption of finite resources and the growing climate crisis necessitate innovative manufacturing waste management approaches. This study investigates the untapped potential of redesigning waste materials—specifically, pre-consumer waste or "new waste"—to create value while mitigating environmental impact. Unlike recycling or disposal, this approach leverages the inherent qualities of discarded manufacturing materials derived from virgin resources, aligning with the European Union’s waste hierarchy principles. Using a multiple case study methodology, we analysed eight collaborations between manufacturing companies and industrial designers. The actor-resources-activities model was employed to understand how these partnerships foster redesign and prolong material lifespans. Our findings reveal that strategic actor roles and interactions are crucial in activating redesign potential, enabling the transformation of waste materials into new products. The crucial actor roles consist of an industrial designer, a waste owner, a waste processor, and a sales & distribution actor. The results highlight significant business and environmental opportunities, including cost reductions and waste diversion from landfills. However, realising this potential requires targeted interventions to facilitate cross-disciplinary collaborations and align objectives among stakeholders. By illustrating successful constellations of actors and processes, this research provides actionable insights into unlocking new avenues for circular economy practices in manufacturing.